Methylation of Immune-Related Genes in Peripheral Blood Leukocytes and Breast Cancer - Tian, Tian; Fu, JinMing; Li, DaPeng; Liu, YuPeng; Sun, HongRu; Wang, Xuan; Zhang, XianYu; Zhang, Ding; Zheng, Ting; Zhao, Yashuang; Pang, Da (Frontiers in Oncology, 2022)
Abnormal DNA methylation contributes to breast cancer (BC). Immune-related genes play crucial roles in BC development and progression. This study is to investigate the effect of methylation of immune-related genes in peripheral blood leukocytes (PBLs) on BC risk. GSE51032 and GSE104942 datasets were used to identify significantly differentially methylated CpG sites (DMCs) of immune-related genes. A case–control study was conducted using MethylTarget sequencing to validate the relationship between the methylation levels of the screened genes and BC risk. We also evaluated the association between methylation haplotypes of screened genes and BC risk. Moreover, we sorted the blood leukocytes into T cells, B cells and monocytes to detect the difference of DNA methylation in different cell subtypes. A total of five DMCs were screened from GEO datasets, including cg01760846 (PSMC1), cg07141527 (SPPL3), cg15658543 (CARD11), cg21568368 (PSMB8), cg24045276 (NCF2). In the case-control study, there were significant associations between methylation of the CpG sites in the five genes and BC risk. Methylation haplotype burdens of PSMC1, CARD11 and PSMB8 were associated with reduced BC risk. Moreover, there were heterogeneities in the methylation levels of the genes in different cell subtypes. In conclusion, methylation of PSMC1, SPPL3, CARD11, PSMB8 and NCF2 in PBLs were associated with BC risk. The five genes methylation could be the potential biomarkers for predicting BC risk.